Using the E-Netsim application for visual simulation of the movement of the autonomous robots - Protsenko, Andrii; Ivanov, Valeriy (Сучасні інформаційні системи, 2022)
The main task of path search methods is to generate a possible path through a section of the environment while bypassing obstacles and minimizing the path length. Existing methods focus on the shortest geometric path to the target and do not take into account various parameters, such as energy consumption or the complexity of sections of the path. This article proposes a method for finding a path and determining its optimality using Petri nets. In addition to generating solutions based on several parameters, this method allows you to expand the visual feedback. When calculating the optimality of the model using the geometric distance from the entry point of the robot to the goal along a certain route and the cost of the abstract amount of energy to move each route. The object of research is Petri nets and their use to model the process of creating routes and finding a way for autonomous robots. The subject of research is the mathematical apparatus of Petri nets and the feasibility of their use in modeling the process of creating routes and finding a way for autonomous robots. The research aims to demonstrate the benefits of Petri nets for visual modeling of the process of finding the path and motion of autonomous robots. Conclusions. The presented technique is suitable for use in modeling the process of finding a way and provides comprehensive statistics for further processing and analysis.